If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 = 12 + 10x Reorder the terms: -4 + 6x = 12 + 10x Solving -4 + 6x = 12 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -4 + 6x + -10x = 12 + 10x + -10x Combine like terms: 6x + -10x = -4x -4 + -4x = 12 + 10x + -10x Combine like terms: 10x + -10x = 0 -4 + -4x = 12 + 0 -4 + -4x = 12 Add '4' to each side of the equation. -4 + 4 + -4x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + -4x = 12 + 4 -4x = 12 + 4 Combine like terms: 12 + 4 = 16 -4x = 16 Divide each side by '-4'. x = -4 Simplifying x = -4
| 300=-6(6-8n) | | -16t^2+40t+7=0 | | -4=12+6x | | ax^2+3ax-21+2a^2-4a=0 | | 7P=6(1-P) | | x^2-19x+80+8=0 | | (3xy^2)-(5x^2y)+(3xy)-(2x^2y^2)=0 | | (-9)(-9)4=m | | x^2+18x+95=0 | | 5(-7)(-4)=n | | y=x^2+18x+95 | | (-7)(-7)2=m | | 3xy^2-5x^2y+3xy-2x^2y^2=0 | | 2(8c+5)= | | 49x^2+1=0 | | 9(b-4)= | | 5(a+5)= | | 8(x+5)=9(x+5) | | 6+y=13 | | 4x=6x+12 | | 5a=7a-14 | | 3x-9c=6bx | | 4z+5=17 | | 4x+3y=57 | | x-9=9-9 | | x^4+27=0 | | 4x+30=x | | 4x-8y= | | -7m-8m-9m= | | 8+x-20=40 | | 4.5y=6x+3 | | 15x+20x+x= |